SHEAR TEST OF BROKEN ROCK IN LABORATORY - Suryaputra, Saviqri
Shear strength as one of rock’s mechanical properties is one of the most significant factors that affect pile slope stability. On previous related crushed rock shear strength research with Barton and Kjaernsli (B&K) criterion, one of the tests that needs to be conducted for shear strength characteristic estimation is the field-scale tilt test that requires a lot of expense and material. Furthermore, majority of mining practicioners in Indonesia prefer to estimate the crushed rock shear strength from intact rock direct shear test residual data using MohrCoulomb (M-C) criterion because it is relatively easier and faster, but there is a risk of less representative obtained result. In this research, a laboratory scale direct shear test is conducted toward crushed mudstone type of rock with an expectation of representing the field-scale tilt test efficiently and producing crushed rock shear strength estimation with B&K criterion that is more representative than M-C one. In addition, crushed rock shear strength with B&K criterion that is built by back calculating the equivalent roughness (R) value is compared to the one from empirical R value. Lastly, numerical modelling using distinct element method is conducted to model the laboratory scale direct shear test of crushed rock and to model the field-scale tilt test for validating purpose in which peak shear stress (?peak) discrepancy is observed. Crushed rock shear strength characteristic that is obtained with B&K criterion under low normal stress (?n) has a smaller value compared to residual shear strength of intact rock that is obtained with M-C criterion and the resulted shear strength (?) differences tend to be larger. In contrary, rising the ?n is resulting smaller ? difference. The ?peak comparison that is from laboratory scale of crushed rock direct shear test numerical model, field-scale tilt test numerical models, crushed rock direct shear test, and analytic equation from the gathered actual laboratory tests data shows variations of under 11,70%.